1995
DOI: 10.1002/jor.1100130403
|View full text |Cite
|
Sign up to set email alerts
|

Effects of excimer laser on healing of articular cartilage in rabbits

Abstract: This study examined healing of 1.0 mm diameter defects in rabbit knee articular cartilage for as long as 14 weeks after creation of the defects by either laser or drilling. The purpose of the research was to determine the effects of laser debridement of cartilage on the intrinsic biomechanical properties of the repair tissue. We therefore imitated chondral shaving and subchondral abrasion of cartilage by creating partial-thickness and full-thickness cartilage defects of standardized size with both excimer lase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0
2

Year Published

2001
2001
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 26 publications
0
19
0
2
Order By: Relevance
“…61,62 Experiments in rabbits demonstrated the growth of neogenetic cartilage after nonablative laser treatment of the spinal disks in only the irradiated zones. 55,73,78,79 The histological and electron microscopic examinations verified formation of hyaline-like and fibrous-hyaline cartilages (Figs. 7 and 8) in the modeled defects of the NP in two and six months after laser treatment.…”
Section: Laser Reconstruction Of Spine Disksmentioning
confidence: 92%
See 2 more Smart Citations
“…61,62 Experiments in rabbits demonstrated the growth of neogenetic cartilage after nonablative laser treatment of the spinal disks in only the irradiated zones. 55,73,78,79 The histological and electron microscopic examinations verified formation of hyaline-like and fibrous-hyaline cartilages (Figs. 7 and 8) in the modeled defects of the NP in two and six months after laser treatment.…”
Section: Laser Reconstruction Of Spine Disksmentioning
confidence: 92%
“…It was concluded that many studies are not scientifically substantiated and future investigations should be based on sound biological foundations. Later, Athanasiou et al 73 studied the effect of an excimer laser on the healing of articular cartilage in a rabbit's knee. Chondral shaving and subchondral abrasion of cartilage, by creating partial-thickness and full-thickness cartilage defects of standardized size, were imitated with both an excimer laser and drilling.…”
Section: Experimental and Clinical Studies Prospects Of Laser Regenementioning
confidence: 99%
See 1 more Smart Citation
“…Associated with the abnormal composition of such repair tissue is a deficiency in biomechanical function [2,15,46]. Because of the ineffectiveness of intrinsic repair, methods for stimulating cartilage repair are under active investigation…”
Section: Introductionmentioning
confidence: 99%
“…In particular, the objectives were (1) to determine the effects of culture conditions (serum and duration of culture) on the formation of a CM by adult bovine chondrocytes; (2) to optimize the formation of a cartilaginous tissue by the chondrocytes after their recovery from the alginate gel; (3) and to determine if the proteoglycan (PG) and collagen components that accumulate into the matrix of the cartilage constructs are representative of those present in native articular cartilage.…”
Section: Introductionmentioning
confidence: 99%